Terahertz radiation generation by the beating of two cross focused Gaussian laser beams in axially magnetized plasma. (4th November 2015) - Hussain, Saba; Kishor Singh, Ram; Sharma, R. P.
Abstract: This paper presents a theoretical model for the generation of right circularly polarized terahertz (THz) radiation by the beating of two cross focused Gaussian laser beams, in axially magnetized plasma. The presence of a finite ponderomotive force causes the redistribution of charge carriers, which changes the dielectric constant and results in cross focusing of the laser beams. The results reveal that the presence of a static magnetic field significantly enhances the cross focusing of the beams. Due to the mutual interaction between the focused beams, the electrons also experiences a nonlinear force at the beat wave frequency. The nonlinear velocity component at the beat wave frequency then couples with the pre-existing density ripple and results in a nonlinear current density generation at THz frequency. The yield of the generated THz radiations strongly depends on the magnitude of the background magnetic field and cross focusing of the laser beams.